Rancang Bangun Detektor Kematangan Buah Kelapa Sawit Menggunakan Sensor Tcs3200 Dan Modul Wifi ESP32-CAM dengan Notifikasi via Telegram - Aldhi Cahyo Millenio Putro; Rahmat Rasyid (Jurnal Fisika Unand, 2024)
This study aims to make a detector of oil palm fruit maturity using the TCS3200 color sensor and the ESP32-CAM Wi-Fi module with notifications via Telegram. Oil palm farmers need a tool to detect the ripeness of the fruit to make it easier for them to monitor the fruit. This tool uses the TCS3200 color sensor to detect the ripeness of palm fruit based on the color of the palm skin; at the same time, the ESP32-CAM module is useful for processing data from the TCS3200 color sensor as the output of Telegram notifications. The TCS3200 color sensor detects the RGB value of the palm object, which is then processed by the ESP32-CAM module. The results obtained in testing the maturity detection tool for palm fruit in ripe and immature conditions can be seen from the Telegram notification. The RGB value of the TCS3200 color sensor will be displayed as information on the condition of the palm fruit, which is detected and used as a notification on the Telegram application. The highest percentage of success in testing the maturity of the fruit was when the fruit was immature at 100%, and the lowest was when the fruit was ripe at 86.6%.